TRENDS OF SYPHILIS AMONG BLOOD DONORS AT A TERTIARY CARE CENTER IN WESTERN RAJASTHAN: AN OBSERVATIONAL STUDY WITH SPECIAL REFERENCE TO THE IMPACT OF COVID-19 - Bharti, Arun; Alha, Sonam; Mathur, Rishi; Mahawar, Novrang Lal; Seegar, Hemant (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This observational study aimed to determine the prevalence and trends of syphilis among blood donors at a tertiary care center in Western Rajasthan and assess the impact of the COVID-19 pandemic on testing and diagnosis rates. Methods: The study included 208,264 blood donors who donated blood at the blood center from 2017 to 2022. The blood samples were tested for all mandatory transfusion-transmitted infections (TTIs), including syphilis. Data were analyzed using descriptive statistics. Results: The overall seropositivity of TTIs was 1.97%, with a moderate prevalence of syphilis among blood donors. The percentage of syphilis-positive samples varied each year, with the highest percentage in 2020 (1.02%) and the lowest in 2019 (0.68%). The study found decreasing trends of syphilis prevalence among blood donors over the years. However, the percentage of positive samples in 2020 was higher than in the other years, potentially due to the impact of the COVID-19 pandemic. Conclusion: The study provides valuable insights into the prevalence and trends of syphilis among blood donors in Western Rajasthan and the impact of the COVID-19 pandemic on testing and diagnosis rates. The findings may inform strategies for maintaining access to sexual and reproductive health services during times of crisis, as well as for the prevention and control of syphilis in the region.